2019
DOI: 10.3390/ijms20092258
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade for Advanced NSCLC: A New Landscape for Elderly Patients

Abstract: The therapeutic scenario for elderly patients with advanced NSCLC has been limited to radiotherapy and chemotherapy. Recently, a novel therapeutic approach based on targeting the immune-checkpoints has showed noteworthy results in advanced NSCLC. PD1/PD-L1 pathway is co-opted by tumor cells through the expression of PD-L1 on the tumor cell surface and on cells within the microenvironment, leading to suppression of anti-tumor cytolytic T-cell activity by the tumor. The success of immune-checkpoints inhibitors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Further evaluations showed that plasma concentrations of IL2, IL7, IL10, GCSF, IP10, MCP1, MIP1A, and TNFα were higher in ICU patients than non-ICU patients [50]. The chaotic increase of excessive cytokines produces a cytokine storm which, along with disruption of anti-inflammatory mechanisms, may prompt an imbalance in coagulative axis resulting in fatal outcomes [51][52][53][54][55][56][57] (Fig. 1).…”
Section: Sars-cov-2 Pathogenesis: Implications For Older Adultsmentioning
confidence: 99%
“…Further evaluations showed that plasma concentrations of IL2, IL7, IL10, GCSF, IP10, MCP1, MIP1A, and TNFα were higher in ICU patients than non-ICU patients [50]. The chaotic increase of excessive cytokines produces a cytokine storm which, along with disruption of anti-inflammatory mechanisms, may prompt an imbalance in coagulative axis resulting in fatal outcomes [51][52][53][54][55][56][57] (Fig. 1).…”
Section: Sars-cov-2 Pathogenesis: Implications For Older Adultsmentioning
confidence: 99%
“…Currently, targeted therapies, including those based on the use of EGFR-tyrosine kinase inhibitors (TKIs), BRAF inhibitors, and ALK inhibitors, have demonstrated promising efficacy, with a 60–80% response rate and 9–30 months of progression-free survival in treating advanced NSCLC with relevant driver mutations [ 6 , 8 , 9 ]. Immunotherapy using anti-PD-1/PD-L1 immune checkpoint inhibitors has been developed as a new therapy for metastatic NSCLC that has demonstrated efficacy in numerous clinical trials in which a 15–45% objective response rate was observed in addition to prolonged overall survival [ 7 , 10 , 11 , 12 ]. However, some NSCLC patients still do not have targetable driver mutations and do not benefit from immunotherapy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With age, immune system function is impaired and disrupts the expression of PD-1 and CTLA-4, so the ability to respond to immunotherapy may be altered. Other important age-related changes are: (i) a reduction in CD8 + naïve T cell population; (ii) a stable proportion of CD4 + naïve T cells but with an altered function; (iii) a rise of memory CD4 + T cells and (iv) a higher concentration of inflammatory cytokines [88]. In this context, Kornelis and colleagues studied CD 161 + (C-type lectin receptor) T cells population, which identifies subsets of CD4 + and CD8 + T cells with a strong pro-inflammatory phenotype, in peripheral blood of elderly patients.…”
Section: Discussionmentioning
confidence: 99%